Kinetika Adsorpsi Antibiotik Tetrasiklin Oleh Komposit TiO2-Ni/PVA/Serat Sabut Pinang Teraktivasi - Povi, Povi; Wahyuni, Nelly; Zaharah, Titin Anita (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Environmental pollution from tetracycline antibiotics has become a serious concern because of their stability and tendency to bind to Ca2+ and other ions, leading to frequent detections in wastewater, surface water, groundwater, sludge, and sediments. One effective method to address this issue is adsorption using TiO2-Ni-based composite materials. This study aims to investigate the effect of variations in polyvinyl alcohol (PVA) mass on the adsorption capacity and rate of tetracycline in TiO2-Ni/PVA/activated areca fiber composites. TiO2-Ni/activated areca fiber was composited with PVA at mass ratios of 1, 2, and 3 and then tested in a tetracycline solution for 5 hours. Kinetic data were analyzed using first-order, second-order, pseudo-first-order, and pseudo-second-order models. The results showed that increasing PVA mass enhanced the adsorption percentage, with the highest value observed at 3 grams of PVA, reaching 12.60% after 5 hours of contact. The kinetic pattern of TiO2-Ni/PVA/activated areca fiber composites with 1 and 2 grams of PVA followed the pseudo-first-order adsorption model. In contrast, the composite with 3 grams of PVA tended to follow the first-order adsorption model.